Cardiac arrhythmias that masquerade as epilepsy. Issue 6074 (4th June 1977) - Schott, G D; McLeod, A A; Jewitt, D E
Abstract : Over six months 10 patients, representing 20% of those referred to a neurological department with possible idiopathic epilepsy, were subsequently considered to have cardiac arrhythmias that caused or significantly contributed to their symptoms. In some cases relevant arrhythmias were shown only after prolonged electrocardiographic monitoring. Although several theoretical and practical factors need to be assessed when considering the cardiac basis for cerebral disturbances, unsuspected cardiac arrhythmias may underlie "epilepsy" in many patients.